Samarium(II) Monoalkyl Complex Supported by a β‐Diketiminato‐Based Tetradentate Ligand: Synthesis, Structure, and Catalytic Hydrosilylation of Internal Alkynes. Issue 24 (15th April 2020) - Liu, Xiaojuan; Wen, Qingqing; Xiang, Li; Leng, Xuebing; Chen, Yaofeng
Abstract: The synthesis and catalytic applications of trivalent rare‐earth metal alkyl complexes have been well developed, but the chemistry of divalent rare‐earth metal alkyl complexes lagged much behind. Herein, we report the synthesis, structure, and catalytic applications of a samarium(II) monoalkyl complex supported by a β‐diketiminato‐based tetradentate ligand, [LSmCH(SiMe3 )2 ] (L=[MeC(NDipp)CHC(Me)NCH2 CH2 N(Me)CH2 CH2 NMe2 ] −, Dipp=2, 6‐( i Pr)2 C6 H3 ). This complex is synthesized by the salt metathesis reaction of samarium iodide [LSm( μ ‐I)]2 and KCH(SiMe3 )2 in 63 % yield. Its structure is characterized by single‐crystal X‐ray diffraction, showing a distorted square‐pyramid coordination geometry. This samarium(II) monoalkyl complex exhibits high catalytic activity in the hydrosilylation of aryl and methyl‐substituted unsymmetrical internal alkynes with secondary hydrosilanes, selectively providing the α‐( E ) products in high yields. Abstract : A five‐coordinate samarium(II) monoalkyl complex is synthesized and structurally characterized. This complex shows high catalytic activity and high stereo‐ and regioselectivity in the hydrosilylation of various aryl and methyl‐substituted unsymmetrical internal alkynes with secondary hydrosilanes under mild conditions (see scheme).